Population and Nesting Site Evidence for Diamondback Terrapins, Malaclemys terrapin, in Northeast Florida - Butler, Joseph A.; Lambert, J. David; DeDeo, Michelle; Murphy, Daniel P. (Frontiers in Ecology and Evolution, 2022)
Abstract The primary objective of this study was to locate populations and nesting areas of Diamondback Terrapins in the four northeastern-most counties of Florida (Nassau, Duval, St. Johns, and Flagler). We used head counts from the boat and land surveys of shorelines and high spots that could possibly support nesting to establish terrapin presence. During the land surveys we searched for crawls, intact and depredated nests, dead terrapins, and terrapin bones. To evaluate whether woody plant presence affected nest site choices, we recorded the occurrence of 10 common woody species during each land survey and compared areas where nesting did and did not occur. We collected 404 terrapin records in 2013 and 2014. Most were from Nassau County (277) and only one was from Flagler County. Most data were in the form of depredated nests (205) and terrapin remains (147). The woody plant data suggest that terrapins were significantly more likely to nest when Christmas Berry (Lycium carolinianum) was present, and nesting was less likely when either Wax Myrtle (Myrica cerifera) or Oak (Quercus spp.) were present.